2020
DOI: 10.3390/genes11040375
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variants in GDF9 Gene Affect Promoter Activity and Litter Size in Mongolia Sheep

Abstract: Litter size is an economically important trait in sheep breeding. The objectives of this study were as follows: (1) to ascertain if any of the 19 known variants in the BMPRIB, BMP15, and GDF9 genes are present and associated with the litter size of Mongolia sheep; (2) to identify novel variants in GDF9 and perform association analysis; and (3) to validate the effects of these GDF9 promoter variants on the activity of the gene. The results of the 19 known variants showed that the FecBB affected the litter size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
(79 reference statements)
2
18
0
1
Order By: Relevance
“…In this study, litter size was significantly affected by G1 point mutation of GDF9 gene, where heterozygous genotypes presented higher litter size (1.386±0.046) compared to the wild-type genotype (1.247±0.033) and homozygous carrier ewes (1.040±0.094). This result is in agreement with those obtained in Belclare and Cambridge breeds [22], Romanov sheep [23], and Mongolia sheep [49]. However , Liandris et al [42] reported a non-significant association between the mutation in the GDF9 gene and litter size in Karagouniki breed.…”
Section: Source Of Variation Df Sm Ms F-ratio Pr>fsupporting
confidence: 91%
“…In this study, litter size was significantly affected by G1 point mutation of GDF9 gene, where heterozygous genotypes presented higher litter size (1.386±0.046) compared to the wild-type genotype (1.247±0.033) and homozygous carrier ewes (1.040±0.094). This result is in agreement with those obtained in Belclare and Cambridge breeds [22], Romanov sheep [23], and Mongolia sheep [49]. However , Liandris et al [42] reported a non-significant association between the mutation in the GDF9 gene and litter size in Karagouniki breed.…”
Section: Source Of Variation Df Sm Ms F-ratio Pr>fsupporting
confidence: 91%
“…The possible reason is the transcriptional silencing caused by chromatin condense after nuclear membrane breakdown [22] and that deposited maternal RNAs were selectively degraded during the GV to MII transition [23]. Maternal genes play important roles in oocyte maturation, and GDF9 and BMP15, which are considered essential during oocyte development, maturation, and fertilization, were also identified in a comparison of bovine GV and MII oocytes [15,[24][25][26][27]. Down-regulating GDF9 can induce intraovarian hyperandrogenism and finally lead to follicular arrest [28].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, many mutations in the gene were identified in Belclare sheep ( FecG F ) [ 4 ] of Europe, Iranian Afshari sheep (G2, G3, and G4) [ 5 ] and Fat-Tailed sheep (G1, G2, G3, and G4) [ 6 ] of Middle Eastern origin, and Rahmani sheep ( FecG H ) [ 7 ] of Africa. It was reported that c.978A>G and c.994G>A, FecG H , c.1040T>C (Phe 347 Ser) were associated with litter size in Araucana creole, Rahmani, and Mongolia sheep [ 7 , 8 , 9 ], respectively.…”
Section: Introductionmentioning
confidence: 99%